The Role of Rohis' Extracurricular Activities in Instilling Moderate Character in Students - Divana Nur Maulida; Dartim Dartim (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Character education is a crucial aspect in shaping students into moderate and noble individuals, especially within the context of social and cultural diversity. The Islamic Spiritual Extracurricular Program (ROHIS) at SMK Negeri 1 Surakarta serves as a strategic platform to instill religious values and moderation through various activities such as moral studies, case discussions, religious training, and social engagement. This study aims to examine the role of ROHIS activities in shaping students’ moderate character and to identify the challenges faced in its implementation. Using a case study approach and qualitative data, the findings reveal that ROHIS activities are effective in enhancing attitudes of tolerance, mutual respect, and social sensitivity, as well as in sustainably fostering students' character development. However, challenges such as the influence of extremist ideologies from social media, limited facilities, and low student participation require serious attention to ensure that development strategies can be carried out optimally. It is recommended that schools enhance program innovation, involve parents, utilize digital media, and conduct regular evaluations to strengthen the role of ROHIS in cultivating a strong sense of moderation among students